2004
DOI: 10.5194/angeo-22-3799-2004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of the field-aligned E-layer irregularities observed by the Gadanki VHF radar

Abstract: Abstract. We report on the field-aligned irregularities observed in the low-latitude sporadic E-layer (Es) with the Gadanki (13.5 • N, 79.2 • E; geomagnetic latitude 6.3 • N) VHF radar. The radar was operated intermittently for 15 days during the summer months in 1998 and 1999, for both daytime and nighttime observation. The total observation periods are 161 h for the nighttime and 68 h for the daytime.The observations were used to study the percentage of occurrence of the E-region echoes for both daytime and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Echoing layers having thickness of 2-3 km and descent rate of ∼0.5 m/s have already been reported from Gadanki observations (Choudhary et al, 1996;Patra et al, 2004;Pan and Rao, 2004). However, such echoes during daytime have been observed at Gadanki only.…”
Section: Discussionmentioning
confidence: 82%
“…Echoing layers having thickness of 2-3 km and descent rate of ∼0.5 m/s have already been reported from Gadanki observations (Choudhary et al, 1996;Patra et al, 2004;Pan and Rao, 2004). However, such echoes during daytime have been observed at Gadanki only.…”
Section: Discussionmentioning
confidence: 82%
“…The morphology of these echoes was also described by Pan and Rao (2003), who showed that these echoes have different appearances at lower latitudes. Woodman et al (1991) and later had explained the generation of these echoes by atmospheric gravity waves modulating the sporadic E-layers (E s ) in such a way so as to make them locally unstable by the gradient drift instability.…”
Section: Introductionmentioning
confidence: 82%
“…lat. 6.5°N) which is close to magnetic equator, multiple FAI layers were observed (e.g., Pan & Rao, 2004). Due to a lack of interferometry, the spatial structures of the FAI layers in horizontal plane were not investigated.…”
Section: Discussionmentioning
confidence: 99%